2011
DOI: 10.1007/s00705-011-1164-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid synthase by amentoflavone reduces coxsackievirus B3 replication

Abstract: Coxsackievirus B3 (CVB3) is a human pathogen that causes acute and chronic infections, but an antiviral drug to treat these diseases has not yet been developed for clinical use. Several intracellular pathways are altered to assist viral transcription, RNA replication, and progeny release. Among these, fatty acid synthase (FAS) expression is increased. In order to test the potential of FAS inhibition as an anti-CVB3 strategy, several experiments were performed, including studies on the correlation of CVB3 repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…Dynamin 2 protein encoded by DNM2 is required for CVB3 entry (Patel et al 2009). Fatty acid synthase encoded by FASN is required for CVB3 replication (Wilsky et al 2012). OSBP and SACM1L are required for sterol/PI(4)P exchange at the ERGolgi interface, and rhinovirus and enterovirus, which belong to Picornaviridae like CVB3, use these processes for viral replication (Mesmin et al 2013;Roulin et al 2014;Strating et al 2015).…”
Section: Dnm2 Fasn Osbp and Sacm1l Are Known To Be Important For Ementioning
confidence: 99%
“…Dynamin 2 protein encoded by DNM2 is required for CVB3 entry (Patel et al 2009). Fatty acid synthase encoded by FASN is required for CVB3 replication (Wilsky et al 2012). OSBP and SACM1L are required for sterol/PI(4)P exchange at the ERGolgi interface, and rhinovirus and enterovirus, which belong to Picornaviridae like CVB3, use these processes for viral replication (Mesmin et al 2013;Roulin et al 2014;Strating et al 2015).…”
Section: Dnm2 Fasn Osbp and Sacm1l Are Known To Be Important For Ementioning
confidence: 99%
“…For example, DENV and WNV recruit fatty acid synthase (FASN), the key enzyme in FA biogenesis, to VRCs[44,55,56]. In line with a requirement for de novo FA biosynthesis, several viruses, including enteroviruses, DENV, WNV and HCV, are sensitive to pharmacological inhibition of FASN and in some cases upregulate FASN[44,53,[55][56][57][58][59][60].…”
mentioning
confidence: 99%
“…The study showed that the mice infected with CVB3 had defects in their blood circulation, and viral replication was found in their heart and kidneys (Yin et al ., 2014). Although the anti-CVB3 activity of amentoflavone was also suggested to be mediated by the inhibition of fatty acid synthase expression (Wilsky et al ., 2012), amentoflavone possessed higher cytotoxicity with relatively weaker antiviral activity than the total flavonoid extracts from Selaginella moellendorffii Hieron (Yin et al ., 2014). Thus, it seems that there may be a synergistic effect exerted by flavonoids, or other antiviral compounds may be present in the total flavonoid extracts from Selaginella moellendorffii Hieron.…”
Section: Discussionmentioning
confidence: 99%